OP0023 Germinal and Somatic Genetic Variants of TNFAIP3 Promote Lymphomagenesis Process Complicating Primary Sjögren's Syndrome. (23rd January 2014) - Nocturne, G.; Boudaoud, S.; Miceli Richard, C.; Viengchareun, S.; Lazure, T.; Nititham, J.; Taylor, K. E.; Criswell, L. A.; Ma, A.; Busato, F.; Melki, J.; Dubost, J. J.; et al.
Abstract : Background: The pathophysiology of lymphomas in auto immune disease (AID) involves persistent inflammation and activation of autoimmune B cells leading to NF-kB activation. The TNFAIP3 gene encodes the A20 protein, a central gatekeeper of NF-kB activation. Germinal abnormalities in TNFAIP3 have been associated with different AID and somatic mutations of the gene have been observed in several lymphoma subtypes, particularly MALT lymphoma, the lymphoma subtype most frequently associated with pSS. Objectives: To investigate whether TNFAIP3 abnormalities are involved in the lymphomagenesis process in pSS. Methods: The discovery set was constituted by 584 pSS patients including 25 patients with lymphoma and 451 controls of Caucasian ancestry, addressed by 48 Ancestry Informative Markers. Three SNPs encompassing the TNFAIP3 locus located on 6q23 (rs13192841, rs2230926 and rs6922466) and known to be associated with SLE and RA were genotyped. 19 additional patients with pSS and lymphoma were used for extension and replication. We sequenced all TNFAIP3 exons in germinal and lymphoma DNA from 20 pSS patients with lymphoma. Functional abnormalities of A20 were assessed by gene reporter assays. Results: The 3 TNFAIP3 SNPs were not significantly associated with risk of pSS. But multivariate analysis demonstrated a significant association between the rs2230926 SNP (coding for an amino acid substitution in exon 3) and pSS complicated by lymphoma: OR vs controls = 3.36 (95%CI 1.34 - 8.42) p= 0.0097, OR vs pSS without lymphoma = 3.26 [95%CI 1.31 – 8.12], p=0.011. TNFAIP3 gene sequencing of germinal DNA from 43 patients with pSS and lymphoma confirmed the more frequent presence of the rs2230926G risk variant in 11/43 patients (25.6%, versus 11% in controls, p=0.018). Twelve of the 20 (60%) patients with paired germinal and lymphoma TNFAIP3 sequence data had functional abnormalities of A20. The frequency was even higher (77%) among pSS patients with MALT lymphoma (n=28). Mutated A20 variants (rs2230926G and GG insertion) were both less effective than the wild type A20 in inhibiting NF-kB-dependent activation (p< 0.0001). Conclusions: This study demonstrates that A20 inactivation plays a key role in lymphomagenesis in the context of autoimmunity. It supports a scenario in which the presence of germinal and/or somatic abnormalities of genes leading to impaired control of NF-kB activation in B cells continuously stimulated by autoimmunity enhances the risk of lymphoma. Disclosure of Interest: None Declared